Analisis Susut Non Teknis dengan Metode Pendekatan Presentase Pembebanan di PT. Delta Dunia Tekstil - Putra, Agus Isa; Djuniadi, Djuniadi (Fakultas Teknik Universitas Muria Kudus, 2024)
As the Electricity is one of the most important needs for human life. PT PLN (Persero) as a company providing electricity needs has an obligation to provide electricity to the people of Indonesia. The loss of energy that occurs in the process of distributing electricity to customers is still one of the main problems that is still being faced by PLN. Therefore, it is necessary to make efforts to reduce the losses so that the reliability of the electric power system is getting better. Currently, an AMR (automatic meter reading) system has been implemented. for calculating distribution losses, customer load analysis, observing effectively the possibility of irregularities in the measurement of electrical energy at customers. This research aims to calculate the amount of non-technical losses and potential losses with the AMR system at PT Delta Dunia Textile. The non-technical shrinkage calculation method used in this study is the loading percentage approach for each phase. After carrying out the measurements, the results were obtained, namely the current in the R phase was not measured, as a result, PT PLN (Persero) UP3 Pekalongan experienced a loss of underbilled power. The reason for not measuring the current in the R phase is because the Current Transformer (CT) cable is almost broken, so you have to rewiring the CT cable again. By implementing this AMR system, it is easy to find out the customer's energy usage load profile data so that when an anomaly occurs in the measuring device it can be handled immediately.